The Development of Interactive Multimedia on Ethnoscience Integrated Acid and Base Material Oriented to Scientific Literacy Capabilities - Mustofa, David Ilham; Zurweni, Zurweni; Sanova, Aulia (Universitas Muhammadiyah Sumatera Utara (UMSU), 2024)
Education is a conscious and planned effort to create an environment and learning process where students actively develop religious spiritual strength, self-control, personality and intelligence. The independent learning curriculum proposes changes to the education system for educational progress that is relevant to modern times. The independent learning goal is to create fun education for teachers and students. . Because chemistry subjects require an understanding of abstract concepts, students often have difficulty understanding them. Ethnoscience integrated learning is a new innovation in the world of education that combines culture and science. The 2022 PISA results show that Indonesian students' reading literacy has decreased by 12 points from the 2018 PISA results. These results also explain that Indonesian students are lower than the global literacy average of 117 points. Sadly, only 25.46% of Indonesian students reach the PISA minimum competency standards for reading. Learning media, or even multimedia, is not only a tool to help teachers, but also increases the literacy and character values of each student. This study aims to determine the effectiveness of using interactive multimedia in integrated acid-base material in ethnoscience which is oriented towards scientific literacy abilities. The method used in this study is to compare data from several relevant journals. This research uses a narrative review approach. This research relies on secondary data such as journals and previous research on the relationship between interactive multimedia, ethnoscience, and scientific literacy. The research results show that interactive multimedia integrated with ethnoscience in acid-base material can influence scientific literacy abilities. This is proven from previous research sources that have been studied. Interactive multimedia with chemistry learning on interesting acid-base material integrated with ethnoscience has the benefit of influencing students' thinking abilities through interactive behavior. Chemistry material presented with an integrated ethnoscience culture can increase students' scientific literacy in learning.